'Rational Overeating' in a Feast-or-Famine World: Economic Insecurity and the Obesity Epidemic - Trenton G. Smith; Steven Stillman; Stuart Craig (Institute of Labor Economics (IZA), 2017)
Obesity rates have risen dramatically in the US since the 1980s, but well-identified studies have struggled to explain the magnitude of the observed changes. In this paper, we estimate the causal impact of economic insecurity on obesity rates. Specifically, we construct a synthetic panel of demographic groups over the period 1988 to 2012 by combining the newly developed Economic Security Index (ESI) with data from the National Health and Nutrition Examination Surveys (NHANES). According to our estimates, increased economic insecurity over this time period explains 50% of the overall population-level increase in obesity.
Keywords: D10; I12; I18; J60; 330; obesity; economic insecurity; economic security index